How to Convert Liquid Fertilizer into Dry Fertilizer in Fertigation for Commercial Vegetable and Fruit Crop Production - Guodong Liu; David Sui; Gary K. England (EDIS)
In recent years, more and more liquid fertilizers have been used in vegetable and fruit production. Typically, UF/IFAS recommendations are expressed as pounds per acre or kilograms per hectare. Thus, conversion either from a dry fertilizer basis (the UF/IFAS recommendation) to a liquid fertilizer basis, or from a liquid fertilizer source to the UF/IFAS recommended nutrient rate is often required for correct application rate. This 5-page fact sheet helps growers understand the conversion method from liquid to dry fertilizer. Written by Guodong Liu, David Sui, and Gary K. England, and published by the UF Department of Horticultural Sciences, April 2012.